Dexamethasone induces primary amnion epithelial cell senescence through telomere-P21 associated pathway†. Issue 6 (30th March 2019) - Martin, Laura F; Richardson, Lauren S; da Silva, Márcia Guimarães; Sheller-Miller, Samantha; Menon, Ramkumar
Abstract: Dexamethasone (Dex), a corticosteroid hormone, is used during the perinatal period to help fetal lung and other organ development. Conversely, Dex-induced cell proliferation has been associated with accelerated aging. Using primary amnion epithelial cells (AECs) from term, not in labor, fetal membranes, we tested the effects of Dex on cell proliferation, senescence, and inflammation. Primary AECs treated with Dex (100 and 200 nM) for 48 h were tested for cell viability (crystal violet dye exclusion), cell cycle progression and/or type of cell death (flow cytometry), expression patterns of steroid receptors (glucocorticoid receptor, progesterone receptor membrane component 1&2), inflammatory mediators (IL-6 and IL-8), and telomere length (quantitative RT-PCR). Mechanistic mediators of senescence (p38MAPK and p21) were determined by western blot analysis. Dex treatment did not induce AEC proliferation, cell cycle, influence viability, or morphology. However, Dex caused dependent telomere length reduction and p38MAPK-independent but p21-dependent (confirmed by treatment with p21 inhibitor UC2288). Senescence was not associated with an increase in inflammatory mediators, which is often associated with senescence. Co-treatment with RU486 produced DNA damage, cell cycle arrest, and cellular necrosis with an increase in inflammatory mediators. The effect of Dex was devoid of changes to steroid receptors, whereas RU486 increased GR expression. Dex treatment of AECs produced nonreplicative and noninflammatory senescence. Extensive use of Dex during the perinatal period may lead to cellular senescence, contributing to cellular aging associated pathologies during the perinatal and neonatal periods. Abstract : Dexamethasone induces telomere-dependent p21 mediated non-replicated and non-inflammatory senescence in fetal amnion epithelial cells.